A fast and effective procedure for the optical efficiency determination of luminescent solar concentrators. (September 2015) - Carlotti, Marco; Fanizza, Elisabetta; Panniello, Annamaria; Pucci, Andrea
Graphical abstract: Highlights: Dye/PMMA thin films were analyzed as luminescent solar concentrators (LSC). PeryRoom allowed for a fast and reliable measurement of the photocurrents. The photocurrents were rationalized by means of a simple but effective model. The method was validated by using a Si-based PV module. The results support the use of peryRoom for the optimization of LSC. Abstract: We introduce a new method for the prompt and effective evaluation of the optical efficiency of different sets of luminescent solar concentrators (LSC) based on dye-doped poly(methyl methacrylate) thin films. The procedure founded on the realization of a home-build apparatus (PeryRoom), which allowed for a fast and reliable measurement of the generated photocurrents profiting of the use of a photodiods system. The photocurrents were analyzed by means of a simple model inspired by the work ofGoetzberger and Greube (1977) and rationalized in terms of different dye characteristics and film thickness. The procedure was eventually validated by comparing the optical efficiencies measured by using a Si-based photovoltaic module. Overall, the present results support the use of PeryRoom for the optimization of the current state-of-art LSC systems.